EFFICIENCY OF USE OF RESOURCES OF AGRICULTURAL ENTERPRISES AND THEIR TECHNOLOGICAL MANAGEMENT - BEREZINA, Liudmyla; BAHAN, Nadiia (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article proves that nowadays it is not enough for agricultural enterprises to have the necessary material, financial and labor resources for effective functioning, it is necessary to know how to use them effectively, and, therefore, to have information about production technologies and their management. Special attention is focused on the indicators of the evaluation of the effectiveness of the use of information resources using the coefficients of completeness of information, contradiction of information, accuracy of information, timeliness and validity of information. It is proposed to evaluate the effectiveness of the use of time resources using the coefficients of the use of the working period, the use of the working day, the use of working time and the use of downtime. A system of innovations recommended for implementation in agricultural enterprises has been developed, which takes into account the specifics of agricultural management and offers measures to improve the innovative management of the production process. The proposed indicators will make it possible to conduct research and evaluate the effectiveness, strengths and weaknesses of resource use, to provide proposals that will improve production and increase the efficiency of resource use through the introduction of innovations, the involvement of the latest technologies, including in the field of technological management. In the future, it is appropriate to develop programs for the development of agrarian enterprises with the aim of increasing the efficiency of resource use through modernization and the introduction of new technologies, taking into account the environmental friendliness of the production process.
Keywords: resources; economic efficiency; information resources; time resources; innovations; agricultural enterprises; technological management